1992
DOI: 10.1002/star.19920440702
|View full text |Cite
|
Sign up to set email alerts
|

Flow Cytometric Determination of Light Scattering and Absorbance Properties of Starch Granules

Abstract: Treatment of samples of digested endosperm with SDS resulted in a homogenous suspension of singlc starch granules that was suitable for analysis by flow cytometry without altering their refractive properties. Flow cytometry can be used for more rapid and accurate enumeration of starch granules than can be achieved with a hemocytometer as with the latter the number of starch granules seems to be underestimated. Moreover. flow cytometric analysis based on forward angle light scatter (FALS) and absorbance propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 9 publications
2
14
0
Order By: Relevance
“…The size of the starch granules has been linked directly with the content of the starch components (Jones et al 1992;Meredith 1981). It has been reported that a smaller starch granule has a higher amylose content than a larger one (Ni et al 2012;Peng et al 1999;Zhang et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The size of the starch granules has been linked directly with the content of the starch components (Jones et al 1992;Meredith 1981). It has been reported that a smaller starch granule has a higher amylose content than a larger one (Ni et al 2012;Peng et al 1999;Zhang et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The granule size is correlated with some physicochemical and functional properties of starch such as granule crystallinity, thermal properties, pasting, swelling, baking, and solubility (D'Appolo and Gilles 1971; Kulp 1973;Langeveld et al 2000;Wong and Lelievre 1982;Zhou et al 2015). Ponte et al (1963) concluded that the percentage of B-type starch granule was significantly correlated with the flour breadmaking quality.…”
Section: Introductionmentioning
confidence: 99%
“…Starch granule number was counted by flow cytometry (Jones et al, 1992). Endosperm cells were digested at 37°C overnight with 1 mL of 20 g L −1 cellulysin in 0.1 M NaOAc buffer (pH 4.7).…”
Section: Methodsmentioning
confidence: 99%
“…Flow analysis and sorting methods have been developed since for purification of thylakoids isolated from mesophyll and bundle sheath cells of maize (84) based on differences in chlorophyll fluorescence spectra. Amyloplasts (starch grains), which are generally grouped with chloroplasts because both represent subsets of the classification of plastids, can be rapidly analyzed using flow cytometry, as described by ISAC member Friedrich Srienc and his coworkers (85). Flow analysis of mitochondria, which are non-fluorescent in their natural state, requires use of added fluorochromes or through in vivo targeting of GFP (86).…”
Section: Flow Analysis and Sorting Of Organellesmentioning
confidence: 99%